Assessment of drug utilization pattern and rationality of drug use in treatment of dilated cardiomyopathy in a tertiary care teaching hospital of rural Bengal - Banerjee, Prasun; Mandal, Ananya; Mukhopadhyay, Dipankar; Gangopadhyay, Tanmoy; Mandal, Sonai; Das, Abhijit (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Dilated cardiomyopathy (DCM) is an important underlying cause of congestive heart failure and/or arrhythmias. The introduction of therapy combining diuretics, digoxin and angiotensin converting enzyme inhibitors (ACEI) has significantly decreased mortality and morbidity. The aim of the study was undertaken to identify the pattern of drugs most commonly prescribed for DCM and to assess the rationality behind such use. Methods: This was a prospective study undertaken between 1st July and 31st August 2015. Prescriptions were reviewed and analyzed using the World Health Organization (WHO) indicators for drug utilization studies. Rationality and cost of therapy per prescription was also evaluated. Results: We encountered 78 patients of DCM in the OPD of Cardiology (prevalence of 4.94%). The average number of drugs per prescription was 6.64. Generic prescriptions were made in 90% encounters. As part of therapy, diuretics and ACE inhibitors or angiotensin receptor blockers, were prescribed in all cases. Our results show a distinctive drug use pattern where beta blockers were used more commonly than digoxin. Other commonly prescribed agents were antiplatelet drugs and statins. Antibiotics were prescribed in 8.7% cases and no injectable drug was prescribed. Average drug cost per encounter was 10.63 INR. Conclusions: To conclude, we found a typical and rational pattern of drug use. Diuretics, ACEI and beta blockers were found to be most commonly used agents. This study provides a clear picture of drug use in this special clinical condition in rural Bengal and paves the way for larger and long term studies.